Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/0269216316659603
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the quality of life of people at the end of life: The McGill Quality of Life Questionnaire–Revised

Abstract: The McGill Quality of Life Questionnaire-Revised improves on and can replace the McGill Quality of Life Questionnaire since it contains improved wording, a somewhat expanded repertoire of concepts with fewer items, and a single subscale for the physical domain, while retaining good psychometric properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 29 publications
4
114
0
Order By: Relevance
“…By contrast, the Missoula-VITAS Quality of Life Index was not used in any of the studies, suggesting that this instrument may need more attention. Instead, other instruments measuring aspects of quality of life were identified in this review, for example, the McGill Quality of Life Questionnaire S22 (Cohen et al, 2017) which has shown strong psychometric properties and has previously been recommended (Selman et al, 2011). (Chochinov, 2002) with permisson from the developer.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the Missoula-VITAS Quality of Life Index was not used in any of the studies, suggesting that this instrument may need more attention. Instead, other instruments measuring aspects of quality of life were identified in this review, for example, the McGill Quality of Life Questionnaire S22 (Cohen et al, 2017) which has shown strong psychometric properties and has previously been recommended (Selman et al, 2011). (Chochinov, 2002) with permisson from the developer.…”
Section: Discussionmentioning
confidence: 99%
“…The attending physician in charge of the patient collected socio-demographic and medical data: age, sex, nationality, mother tongue, marital status, education, profession, primary diagnosis, and co-morbidities. (22). The MQoL-R was developed for the setting of end of life.…”
Section: Socio-demographic and Medical Assessmentsmentioning
confidence: 99%
“…Although many studies have measured quality of life in LTC settings [3844], fewer measured quality of care provided. Most studies that did measure quality of care used nonvalidated assessment tools [4].…”
Section: Introductionmentioning
confidence: 99%